Laws Concerning Mineral and Coal Mining on Community Welfare from an Environmental Ethics Perspective - Taqiyaah, Adzraa; Hidayat, Arif (Universitas Negeri Semarang, 2023)
This study delves into the legal frameworks governing mineral and coal mining operations, focusing on their implications for community welfare through the prism of environmental ethics. Through qualitative research methods with a normative juridical approach, this research scrutinizes the transition from Law Number 4 of 2009 to Law Number 3 of 2020 and evaluates the juridical ramifications of the latter on societal well-being. Drawing on data from library research, legal document analysis, and stakeholder interviews, including perspectives from entities such as Jatam and PT Selo Argodedali, the study offers insights into divergent opinions regarding the efficacy of the legislative revisions. Findings indicate discord between mining entities and communities, with the former advocating for regulatory revisions while the latter perceive losses due to mining activities. Moreover, the study critiques the 2020 Minerba Law for its perceived neglect of environmental ethics, prioritizing exploitative practices over environmental preservation. Ultimately, this research underscores the imperative for legal policies to uphold community welfare in harmony with environmental ethics, as mandated by constitutional provisions.